Unveiling the Interplay: NFTs, Metaverse Hype, and Ether Price Dynamics - Niesłony, Marcel (Odkrywanie wzajemnych powiązań: NFT, Hype Metaverse i dynamika cen Ethereum, 2023)
Examining the connection between Non-Fungible Tokens (NFTs), the Metaverse, and Ethereum (ETH) prices reveals a nuanced relationship. NFTs, unique digital assets stored on the Ethereum blockchain, have seen a surge in global interest since early 2021, particularly on platforms like OpenSea. While there is an initial correlation between ETH price surges and increased NFT sales, a decline in ETH prices later leads to a surge in NFT sales, suggesting increased affordability. In the Metaverse, represented by projects like Decentraland, the relationship between the number of Land units sold and ETH prices is inconsistent. Additionally, examining average LAND prices compared to ETH prices reveals some correlation in specific periods. In summary, the analysis suggests a complex interplay between NFTs, the Metaverse, and ETH prices. While initial trends show correlations, factors like affordability and evolving market dynamics contribute to the nuanced relationship. Understanding these elements is crucial for accurate predictions of their impact on ETH prices.
Niesłony, M. (2023). Unveiling the Interplay: NFTs, Metaverse Hype, and Ether Price Dynamics. In A. Kuźmińska-Haberla, S. Bobowski (Eds.), Ekonomia i międzynarodowe stosunki gospodarcze (pp. 24-36). Wroclaw University of Economic and Business.
Keywords: NFT; Metaverse; ETH; Ethereum